Efektivitas Kombinasi Aromaterapi Jahe dan Akupresur terhadap Penurunan Mual dan Muntah Pascaoperasi dengan Anestesi Spinal - Vermansyah, Alvin; Novitasari, Dwi; Kumala Dewi, Feti (Pustaka Galeri Mandiri, 2026)
Postoperative nausea and vomiting (PONV) are commonly experienced by patients undergoing spinal anesthesia. This condition occurs due to the activation of the vomiting center situated in the medulla oblongata, activated by inputs from the gastrointestinal tract, vestibular apparatus, and the pharmacological effects of anesthetic agents and opioids. This process involves multiple receptor pathways, including dopamine (D2), serotonin (5-HT3), muscarinic (M1), histamine (H1), neurokinin-1 (NK1), and opioid (?) receptors, which collectively regulate emetic reflexes via the Chemoreceptor Trigger Zone (CTZ). Ginger aromatherapy exerts antiemetic effects by suppressing serotonin (5-HT3) receptor activity, thereby diminishing stimulation of the vomiting center. Meanwhile, P6 acupressure influences the autonomic nervous system and promotes beta-endorphin secretion, contributing to the inhibition of nausea and vomiting reflexes. This research sought to evaluate the effectiveness of combining ginger aromatherapy with P6 acupressure in alleviating PONV. This research utilised a quasi-experimental design with a pretest–posttest control group format and included 22 respondents chosen purposively. The assessment of symptoms was carried out using “the Rhodes Index of Nausea, Vomiting, and Retching (RINVR)”. Paired t-test analysis in the intervention group revealed a score reduction from 14.18 to 6.45 (p = 0.000), whereas the control group showed a change from 13.55 to 11.00 (p = 0.001). Independent t-test results on posttest scores confirmed a significant difference between groups (p = 0.000). These findings indicate that the combined intervention is effective in reducing PONV among spinal anesthesia patients